Analisis Strategi Pemasaran Transportasi Online Menggunakan Teori Permainan - Indah Hatika Lubis; Ismail Husein; Rima Aprilia (Department of Mathematics, Hasanuddin University, 2024)
Advances in information and communication technology that are growing rapidly also bring influence in the field of transportation. It can be seen with the emergence of online transportation applications that help people so that it can be easier to order fast and efficient transportation in reaching various places. Along with the many online transportation applications that appear, this makes competition between online transportation increase. For this reason, online transportation companies need the right and best strategy to reach consumer profits and interests. The purpose of this research is to analyze competitive strategies based on optimal online transportation marketing strategies. The solution that can be used for this problem is to use the Game Theory method. Game Theory method is an approach or technique used to analyze the situation of interaction between two or more people or entities that have conflicting interests in choosing the action to be performed. The results of the research obtained show competition between Gojek and Grab, Gojek's optimal strategy is Security and Promo while Grab is Service and Promo. In the competition of Gojek and InDrive, Gojek's optimal strategy is promo, while InDrive is price. In the Gojek and Maxim competition, the same optimal strategy is Promo. On the competition of Grab and InDrive, Grab's optimal strategy is Security, while InDrive is price. In the competition of Grab and Maxim, Grab's optimal strategy is Promo while Maxim is price. In InDrive and Maxim competition, InDrive's optimal strategy is Price, while Maxim is Promo. So, from the research results, it is concluded that gojek has the most profitable marketing strategy if it uses promos, grab uses service and security, maxim uses promos, and indrive uses prices.